'Hit & Run' Model of Closed-Skull Traumatic Brain Injury (TBI) Reveals Complex Patterns of Post-Traumatic AQP4 Dysregulation. Issue 6 (June 2013) - Ren, Zeguang; Iliff, Jeffrey J; Yang, Lijun; Yang, Jiankai; Chen, Xiaolin; Chen, Michael J; Giese, Rebecca N; Wang, Baozhi; Shi, Xuefang; Nedergaard, Maiken
Cerebral edema is a major contributor to morbidity associated with traumatic brain injury (TBI). The methods involved in most rodent models of TBI, including head fixation, opening of the skull, and prolonged anesthesia, likely alter TBI development and reduce secondary injury. We report the development of a closed-skull model of murine TBI, which minimizes time of anesthesia, allows the monitoring of intracranial pressure (ICP), and can be modulated to produce mild and moderate grade TBI. In this model, we characterized changes in aquaporin-4 (AQP4) expression and localization after mild and moderate TBI. We found that global AQP4 expression after TBI was generally increased; however, analysis of AQP4 localization revealed that the most prominent effect of TBI on AQP4 was the loss of polarized localization at endfoot processes of reactive astrocytes. This AQP4 dysregulation peaked at 7 days after injury and was largely indistinguishable between mild and moderate grade TBI for the first 2 weeks after injury. Within the same model, blood–brain barrieranalysis of variance permeability, cerebral edema, and ICP largely normalized within 7 days after moderate TBI. These findings suggest that changes in AQP4 expression and localization may not contribute to cerebral edema formation, but rather may represent a compensatory mechanism to facilitate its resolution.